Pharmacokinetics study of rosamultin, a major bioactive component from the root of Potentilla anserina L. (Rosaceae) by HPLC-MS/MS. Issue 40 (1st October 2019) - Wu, Yuqiang; Wei, Jinxia; Yu, Yingying; Chen, Fei; Li, Xia; Li, Yaxiao; Li, Jianyu; Li, Lingzhi; Zhang, Yongliang
Abstract : Rosamultin is a major active pentacyclic triterpenoid saponin isolated from the root of Potentilla anserina L., which has various pharmacological activities. Abstract : Rosamultin is a major active pentacyclic triterpenoid saponin isolated from the root of Potentilla anserina L., which has various pharmacological activities. So far, the pharmacokinetics of rosamultin have not been studied. Hence, the present study was aimed at the development of a high performance liquid chromatography-tandem mass spectrometry method to quantify the concentration of rosamultin in rat plasma for an in vivo pharmacokinetics study. Plasma samples were prepared by a simple protein precipitation and further purified by solid phase extraction. Kaji-ichigoside F1, an epimer of rosamultin, was chosen as the internal standard. Chromatographic separation was performed on a HPLC XB-C18 column (4.6 × 150 mm, i.d., 3 μm) with a mobile phase consisting of methanol–water–formic acid (63 : 37 : 0.075, v/v/v). Quantification was performed by selected ion monitoring with m / z 673.5 [M + Na] + for rosamultin and the internal standard. The validated method exhibited good linearity over a wide concentration range ( r > 0.9995), and the lower limit of quantification was as low as 5.0 ng mL −1 for rosamultin. The intra- and inter-day precisions (RSD) at all quality control (QC) levels ranged from 3.4–7.7% and 4.3–7.2%, respectively. The accuracy (RE) was from 2.5% to 5.3%. The developed method was rapid, accurate, sensitive and fully validated. It was successfully applied to the pharmacokinetics study of rosamultin in rats after oral administration of rosamultin.